2012
DOI: 10.1136/jnnp-2011-300929
|View full text |Cite
|
Sign up to set email alerts
|

Construction and pilot assessment of the Upper Limb Assessment in Daily Living Scale

Abstract: ObjectiveThe upper limb function of hemiplegic patients is currently evaluated using scales that assess physical capacity or daily activities under test conditions. The present scale, the Upper Limb Assessment in Daily Living (ULADL) Scale, was developed to explore the subjective and objective functional capacities of such patients in a proximal to distal sequence.MethodsA group of experts constructed a scale addressing 17 upper limb functions (five active passive and 12 active) which could be explored by a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…As seen in our results and in previous studies, 8,19,20 changes in fine motor dexterity and hand function are associated with functional impairments in self-care activities. A longitudinal decline in instrumental ADLs usually precedes the decline of basic/self-care ADLs.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As seen in our results and in previous studies, 8,19,20 changes in fine motor dexterity and hand function are associated with functional impairments in self-care activities. A longitudinal decline in instrumental ADLs usually precedes the decline of basic/self-care ADLs.…”
Section: Discussionsupporting
confidence: 77%
“…7 Deficits in fine motor dexterity are associated with functional loss, and are especially impairing of the basic and instrumental aspects of activities of daily living (ADLs). 8 Studies have shown deficits in fine motor skills in patients with AD and MCI. 9,10 However, this evidence comes from complex or experimental motor tasks, involving sophisticated apparatuses usually available only in research settings.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate functional aspects, items of progressively greater difficulty were selected; these reflect a broad range of situations in daily life. It is already known that a VAS can provides a valid measurement of functions and activities (Rousseaux et al, 2012), and is statistically more robust than the Likert-scale. The scale Q and T sections were well accepted by patients.…”
Section: Discussionmentioning
confidence: 99%
“…Visual analog scales have been widely used to assess pain, quality of life assessment, fatigue (Hewlett, Hehir, & Kirwan, 2007) and ADL (Heitz et al, 2010). More recently, a VAS was used to assess upper limb activities in stroke patients (Rousseaux et al, 2012).…”
Section: Scale Design and Developmentmentioning
confidence: 99%
“…A number of reviews have been published to assist the clinician in comparing and contrasting available activity measures, some also describing the development of new assessment tools [3,[28][29][30][31]. A number of reviews have been published to assist the clinician in comparing and contrasting available activity measures, some also describing the development of new assessment tools [3,[28][29][30][31].…”
Section: Box 43 Care and Comfort Measuresmentioning
confidence: 99%